Risk Factors Associated with Post-Cholecystectomy Syndrome and Insights into Post-Surgical Follow-Up: A Retrospective Cohort Study - Prabhu, Prabhu; Prasath E, Ram; Prabhakar, A. (Journal of Neonatal Surgery, 2025)
Background: Post-cholecystectomy syndrome (PCS) encompasses persistent gastrointestinal symptoms following gallbladder removal, with reported incidence varying from 5-40%. This study examines risk factors, etiological patterns, and management outcomes in PCS patients to optimize clinical approaches. Methods: A retrospective cohort study analyzed 40 PCS cases at a tertiary care center. Inclusion criteria comprised patients developing characteristic symptoms (RUQ pain, nausea/vomiting, diarrhea, dyspepsia) ≥5 days post-cholecystectomy. Data on demographics, surgical details, diagnostic workup (USG, MRCP, ERCP), and treatments were extracted from medical records. Statistical analysis identified significant associations. Results: The cohort showed female predominance (70%), mean age 48.5 years, with diabetes prevalent in 35%. Laparoscopic cholecystectomy accounted for 80% of cases. Biliary causes (55%) included retained stones (12.5%) and sphincter of Oddi dysfunction (10%), while non-biliary causes (45%) involved functional disorders. MRCP and ERCP had higher diagnostic yields (62.5% and 37.5%, respectively) than USG. ERCP demonstrated 87.5% therapeutic success, whereas conservative management resolved symptoms in 60%. Significant risk factors included female sex (OR 2.1), diabetes (OR 1.8), and intraoperative complications (OR 3.0). Conclusion: PCS requires tailored diagnostic and therapeutic strategies, with MRCP/ERCP pivotal for biliary etiologies. High-risk patients, particularly women and diabetics, may benefit from proactive monitoring. Endoscopic interventions outperform conservative measures for biliary PCS, underscoring the need for multidisciplinary management. Future prospective studies should standardize diagnostic criteria to refine treatment protocols